Staunch Ships: Due Diligence Equals Absolute Obligation? - Abdul Rahman, Faizah Nazri (Journal of Malaysian and Comparative Law, 2019)
A shipper's rights against the carrier of his goods will normally be contained in the contract evidenced by the bill of lading issued by the carrier upon accepting the shipper's goods for carriage. Where the Hague Rules (hereinafter referred to as 'the Rules') come into the picture, the rights of the shipper for a minimum care regime is guaranteed if certain elements are fulfilled.